The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/bioengineering7040150
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance of Glass Ionomer Cement Restorative Materials

Abstract: In view of the need for aesthetics, restorations of teeth will typically be completed using tooth colored restorative materials. With the advent of biomimetic restorative materials, such as glass ionomer cements (GIC), much greater emphasis is now being placed on how well such materials can resist the challenge of acids that are present in foods and drinks, or gastric contents that are regurgitated. This laboratory study compared the dissolution and behavior of five GIC materials (GC Fuji® VII, GC Fuji® Bulk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
(17 reference statements)
4
17
1
2
Order By: Relevance
“…Furthermore, the present results also reveal how periodic exposure to a low pH solution alone influences some GIC materials, regardless of the medium in which the samples were stored, and again, Equia Forte HT performed better. This is in agreement with Perera et al [47], finding that the more recent GIC materials (GC Fuji Bulk and GC Equia Forte Fil) showed increased acid resistance over the older GIC materials, including Fuji IX. The enhanced formulation of the new generation highly viscous GICs and glass hybrid materials increases strength and acid resistance [47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the present results also reveal how periodic exposure to a low pH solution alone influences some GIC materials, regardless of the medium in which the samples were stored, and again, Equia Forte HT performed better. This is in agreement with Perera et al [47], finding that the more recent GIC materials (GC Fuji Bulk and GC Equia Forte Fil) showed increased acid resistance over the older GIC materials, including Fuji IX. The enhanced formulation of the new generation highly viscous GICs and glass hybrid materials increases strength and acid resistance [47].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with Perera et al [47], finding that the more recent GIC materials (GC Fuji Bulk and GC Equia Forte Fil) showed increased acid resistance over the older GIC materials, including Fuji IX. The enhanced formulation of the new generation highly viscous GICs and glass hybrid materials increases strength and acid resistance [47].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, this research study showed that the mass of samples in all three materials decreased significantly more if exposed to Aceto balsamico vinegar than to Fuzetea and distilled water ( p < 0.05). This is in concordance with Perera et al’s report [ 16 ] and suggests that the availability of hydrogen ions (pH) is related to the extent of a material’s dissolution and disintegration. However, there was no statistically significant difference among the three groups of materials in certain pH environments ( p > 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Exposing standardized GIC samples to acidic load and assessing the change in mass has been well established in previous studies as the method for testing the resistance of GICs to acid [ 15 , 16 ]. The conditioning period of one week at 37 °C allowed stabilization of the acid–base reaction of glass ionomer cements so that water uptake would not affect the mass recordings because it was shown that hygroscopic expansion of GICs occurred in the first 24 h [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation